Public Policy in Malang City - Izzah, Ananda Helena Nurul (Penerbit Goodwood, 2024)
Purpose: This study examines the implementation of legal aid as public policy for underprivileged communities in Malang City, emphasizing its alignment with Law No. 16 of 2011. The research aims to analyze the policy's effectiveness, its benefits to society, and the challenges faced during its implementation. Methodology: This study employs a qualitative approach with a normative research method, also known as a literature study. The research focuses on analyzing academic literature in the fields of public policy and legal aid. Data collection utilizes secondary sources such as government documents and media reports, both printed and electronic. The data is processed into narratives based on theories and concepts of public policy and then interpreted to provide comprehensive insights. No specific tools, brands, or software are mentioned in the document. Results: The study finds that Law No. 16 of 2011 effectively functions as public policy aimed at improving community welfare and ensuring legal equality. However, its implementation faces challenges, including difficulties in obtaining a Certificate of Inability (SKTM) and limited public awareness of legal rights, which hinder equitable access to legal aid. Contribution: This research contributes to the field of public policy and legal studies by providing insights into the intersection of legal frameworks and social equity. It informs policymakers, legal practitioners, and academics about the barriers and potential improvements in delivering legal aid to marginalized groups.